Vulnerability assessment and zoning of developed and susceptible contaminated karstic (Case study: Ravenscar watershed) - asadolah hejazi; zahra heidari (تحقیقات کاربردی علوم جغرافیایی)
In recent years, population growth and consequently the shortage of drinking water resources have increased the importance of studying the areas of caries Regarding the importance of the subject, in the present study, the evaluation and monitoring of the developed karstic areas and the potential of contamination of Cartesian resources in the Ravensar basin have been addressed In this study, 7factors were used to evaluate the factors of Karst development in Ravansar basin as well as two methods of OWA and ANP. The method of work is that after the necessary processing, using the OWA method and applying weights obtained through the ANP model, the zoning is done After designing the zoning map, using the satellite imagery of 2007 and2015, the development of human development areas in the developed karstic areas has been evaluated The results of this study indicate that most of the studied basin, especially in northern and western areas of the basin, are highly and relatively developed in the class, The calculation of the area of man-made areas suggests that in2007, about 2.6 km of occupied areas of man-made industrial zones have been occupied which, according to the growing population, increased to 3.8 km in2015, human-made areas have been extracted in developed artisanal areas